A miR-194/PTBP1/CCND3 axis regulates tumor growth in human hepatocellular carcinoma - Kang, Hoin; Heo, Sungeun; Shin, Jung Jae; Ji, Eunbyul; Tak, Hyosun; Ahn, Sojin; Lee, Kyung Jin; Lee, Eun Kyung; Kim, Wook (Journal of Pathology, 2019)
Polypyrimidine tract-binding protein 1 (PTBP1) is one of the most investigated multifunctional RNA-binding proteins (RBP), controlling almost all steps of mRNA metabolism and processing. It has been reported that PTBP1 is overexpressed in many different types of cancer and this high expression is associated with increased proliferation and poor prognoses. However, there are no reports on a putative role for PTBP1 in the molecular abnormalities and pathogenesis of hepatocellular carcinoma (HCC). Here, we identified PTBP1 as a positive regulator of human HCC growth. The expression of PTBP1 was increased in human HCC cells and tissues compared to the corresponding controls, and this high expression was positively correlated with increased tumor size and a reduced survival rate. Mechanistically, PTBP1 enhanced cyclin D3 (CCND3) translation by interacting with the 5′-untranslated region (5′-UTR) of CCND3 mRNA, consequently facilitating cell cycle progression and tumor growth. Furthermore, we found that miR-194 inhibits PTBP1 expression by binding to the 3′-UTR of PTBP1 mRNA, resulting in reduced CCND3 levels and HCC cell growth; moreover, the levels of PTBP1 were negatively correlated with miR-194 levels in HCC. Taken together, these findings identify PTBP1 as a pivotal enhancer of HCC growth; the miR-194/PTBP1/CCND3 axis seemingly has a crucial role in the development and progression of HCC and targeting the axis could be a novel therapeutic strategy against human HCC. © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
Keywords: 3' Untranslated Regions; 5' Untranslated Regions; Animals; Binding Sites; Carcinoma, Hepatocellular; Cell Line, Tumor; Cell Proliferation; Cyclin D3; Female; G1 Phase Cell Cycle Checkpoints; Gene Expression Regulation, Neoplastic; Heterogeneous-Nuclear Ribonucleoproteins; Humans; Liver Neoplasms; Mice, Inbred BALB C; Mice, Nude; MicroRNAs; Polypyrimidine Tract-Binding Protein; Signal Transduction; Tumor Burden; Tumor Cells, Cultured; CCND3; hepatocellular carcinoma; miR-194; PTBP1; tumor growth